Análisis de la satisfacción al cliente en la empresa CNEL EP Los Ríos - Santana González, Ginger Michael (2021)
The present case study is carried out through a qualitative methodology that allows a review of the situation of the place where the research is carried out, inductive, scientific, bibliographic methods are used, in addition a descriptive study is applied for which the survey technique was adopted, a structured questionnaire was developed that was applied to the users of the company Cnel. EP - Los Ríos, a representative sample was taken using an error of 10% on the population under study. This research is directed to the research line of the Faculty called Administrative Financial Management, Tax Audit and Control and to the research sub-line of the trade career "Marketing and Marketing", the objective of the research is to know the level of satisfaction of the users of the company Cnel. EP - Los Ríos, for which it seeks to answer the following questions: What are the factors that influence customer satisfaction at Cnel. EP - Los Ríos? How does the consumer consider the quality of the service of the company Cnel. EP - Los Ríos?